IL-6/STAT3 Signaling Promotes Cardiac Dysfunction by Upregulating FUNDC1-Dependent Mitochondria-Associated Endoplasmic Reticulum Membranes Formation in Sepsis Mice - Jiang, Tao; Peng, Dewei; Shi, Wei; Guo, Junyi; Huo, Shengqi; Men, Lintong; Zhang, Cuntai; Li, Sheng; Lv, Jiagao; Lin, Li (Frontiers in Cardiovascular Medicine, 2022)
Aims Cytokine storm is closely related to the initiation and progression of sepsis, and the level of IL-6 is positively correlated with mortality and organ dysfunction. Sepsis-induced myocardial dysfunction (SIMD) is one of the major complications. However, the role of the IL-6/STAT3 signaling in the SIMD remains unclear. Methods and Results Septic mice were induced by intraperitoneal injection of LPS (10 mg/kg). Echocardiography, cytokines detection, and histologic examination showed that sepsis mice developed cardiac systolic and diastolic dysfunction, increase of inflammatory cytokines in serum, activated STAT3 and TLR4/NFκB pathway in heart, and raised myocardial apoptosis, which were attenuated by IL-6/STAT3 inhibitor, Bazedoxifene. In vitro, we found that LPS decreased cell viability in a concentration-dependent manner and activated STAT3. Western blot and immunofluorescence results indicated that STAT3 phosphorylation induced by LPS was inhibited by Bazedoxifene. Bazedoxifene also suppressed LPS-induced IL-6 transcription. sIL-6R caused LPS-induced p-STAT3 firstly decreased and then significantly increased. More importantly, we found STAT3-knockdown suppressed LPS-induced expression of FUNDC1, a protein located in mitochondria-associated endoplasmic reticulum membranes (MAMs). Overexpression of STAT3 led to an increase in FUNDC1 expression. Dual-luciferase reporter assay was used to confirm that STAT3 was a potential transcription factor for FUNDC1. Moreover, we showed that LPS increased MAMs formation and intracellular Ca2+ levels, enhanced the expression of Cav1.2 and RyR2, decreased mitochondrial membrane potential and intracellular ATP levels, and promoted mitochondrial fragmentation, the expression of mitophagy proteins and ROS production in H9c2 cells, which were reversed by knockdown of FUNDC1 and IL-6/STAT3 inhibitor including Bazedoxifene and Stattic. Conclusions IL-6/STAT3 pathway plays a key role in LPS-induced myocardial dysfunction, through regulating the FUNDC1-associated MAMs formation and interfering the function of ER and mitochondria. IL-6/STAT3/FUNDC1 signaling could be a new therapeutic target for SIMD.